1965
DOI: 10.1111/j.2044-8260.1965.tb00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Psychological Factors in Religious Conversion

Abstract: A study was made of forty‐three theological students in order to define the factors which had affected their religious experience, in particular, their acquisition of belief. The influence of age, parental belief and family relationships, guilt, neuroticism and extraversion were considered. Those whose conversion was sudden and towards the faith of their parents were found to have high scores on the MPI neuroticism scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

1967
1967
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 2 publications
0
9
1
Order By: Relevance
“…Studies of psychological well-being following conversion have reported the beneficial effects of conversion : theology students who were converts had normal distribution neuroticism scores on the Maudsley Personality Inventory (Roberts, 1965) and lower scores than non-converted theology students (Stanley, 1965) ; Ross (1983) found no evidence of psychopathology among the members of the Hare Krishna temple in Melbourne, while a survey of 2500 respondents to a US women's magazine questionnaire found that converts were happier than non-converts (Shaver, Lenauer & Sadd, 1980). In his recent survey, Bergin (1983) concluded that conversion 'significantly reduces pathological symptoms ', and that converts are 'as functional as or better off than non-converts ', supporting the view of William James, who described conversion as 'the process, gradual or sudden, by which a self hitherto divided and consciously wrong, inferior and unhappy, becomes united and consciously right, superior and happy ' (1902).…”
Section: Religious Change and Mental Healthmentioning
confidence: 99%
“…Studies of psychological well-being following conversion have reported the beneficial effects of conversion : theology students who were converts had normal distribution neuroticism scores on the Maudsley Personality Inventory (Roberts, 1965) and lower scores than non-converted theology students (Stanley, 1965) ; Ross (1983) found no evidence of psychopathology among the members of the Hare Krishna temple in Melbourne, while a survey of 2500 respondents to a US women's magazine questionnaire found that converts were happier than non-converts (Shaver, Lenauer & Sadd, 1980). In his recent survey, Bergin (1983) concluded that conversion 'significantly reduces pathological symptoms ', and that converts are 'as functional as or better off than non-converts ', supporting the view of William James, who described conversion as 'the process, gradual or sudden, by which a self hitherto divided and consciously wrong, inferior and unhappy, becomes united and consciously right, superior and happy ' (1902).…”
Section: Religious Change and Mental Healthmentioning
confidence: 99%
“…Guilt feelings are among the motivational factors that have been investigated. Whereas Clark (1929) found less than 10% of the general population reporting guilt feelings, both Clark (1929) and Roberts (1965) observed about half the converts (both sudden and gradual) in their samples suffering from feelings of guilt prior to their conversion. Roberts (1965) also found that sudden converts who remained within the same faith as their parents were more neurotic than those who were converted to a different faith.…”
mentioning
confidence: 99%
“…vfuereas Clark (1929) found less than 10% of the general population reporting guilt feeling~both Clark (1929) and Roberts (1965) observed about half the converts (both sudden and gradual) in their samples suffering from feelings of guilt prior to their conversion, Salzman (1953) suggested that the sudden conversion was part of the solution to the convert's relations with his father and that when the conversion is to a faith different from his upbringing, neurosis or even psychosis could result" Roberts (1965) tested this prediction and found that the converts vrho reported a sudden conversion experience and who remained within the same faith as their parents were more neurotic than those who were converted to a different faith--quite contrary to Salzman's prediction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The result of this definitional pluralism is that we still know relatively little about the personality correlates of religiosity or religious behaviors. For example, although many studies suggest that religiosity is associated with positive mental health (Allport, 1950;McClain, 1978;Stanley, 1964;Sturgeon & Hamley, 1971), an equal number claim that it is associated with negative mental health (Roberts, 1965;Vine, 1978;see Bergin, 1983, for a review). Clearly, greater attention must be paid to both conever to progress.…”
Section: The Personological Study Of Religious Involvementmentioning
confidence: 99%